Power emission enhancement of light emitting diode by using InN based quantum dot - M. A., Humayun; M. A., Rashid; F., Malek (2015)
This paper highlights the enhancement of emitted power from light emitting diodes using InN based quantum dot in the active layer of the device structure. We have developed mathematical models and analyzed numerically the temperature dependence of the degradation rate of the device lifetime, the effect of light transmission factor and the operating time on the power emitted from the light emitting diodes. The results obtained by using InN based quantum dot in the active layer of the device have been compared with those obtained by using InP based quantum dot in the active layer of the device. The comparison results reveal that the degradation rate of the device has been reduced and the power emission has been enhanced significantly by using InN based quantum dot in the active layer of the device. It can be then concluded that InN based quantun dot will bring a revolusionary changes in the performance improvement of LEDs in the near future.